Dinamika Pembelajaran Pendidikan Agama Islam pada Era Digitalisasi (Studi Kasus di SDN Sarireja I): Penelitian - Endah Robiatul Adawiyah; Anggi Cerlin; Mimin Rukmini; Sandi Iswara (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to explore the dynamics of Islamic Religious Education (PAI) learning in the digitalization era, using a case study at SDN Sarireja I. As technology advances, PAI teachers are required to adapt and utilize digital media in the learning process. This research uses a descriptive qualitative method with data collected through in-depth interviews and observations. The main informants were the principal and Islamic education teachers. The findings indicate that while most teachers still use conventional lecture methods, there is a shift toward digital media usage due to students' high enthusiasm for technology. Challenges include the limited technological proficiency of senior teachers, which is mitigated by younger, tech-savvy teachers. Additionally, Islamic values are integrated not only through PAI lessons but also across various school activities. Student engagement is significantly influenced by the teaching methods applied. A decline in student interest can be addressed through effective classroom management and innovative teaching approaches. This research emphasizes the need for strategic transformation in Islamic education to remain relevant in the digital era.